"Ploughing before Sowing": Trust and the Architecture of the Church Missionary Society (CMS) Medical Missions. Issue 2 (4th May 2019) - Honarmand Ebrahimi, Sara
Abstract: Focusing on the architecture of Church Missionary Society (CMS) hospitals in Isfahan and Kerman (Iran), this article contemplates the issue of gaining the trust of local communities. The issue of gaining trust was frequently discussed in written accounts of the CMS's medical work as a prerequisite for introducing Christian beliefs. The article engages with emerging scholarship under the umbrella term the "history of emotions, " investigating how the hospitals were designed to create an affective connection with local communities. It demonstrates that the missionaries tried to provide a familiar environment by using local architectural elements related to the daily lives of local people. Moreover, instead of importing principles of hospital design from Britain, they actively eschewed them.